On some integral inequalities of Grüss type involving the generalized fractional Saigo k-integral operator - Akhtar Abbas; Shahid Mubeen; Aziz Khan; Thabet Abdeljawad (Heliyon)
Using the generalized Saigo fractional integral operator, the authors of this study prove several novel fractional integral inequalities of the Grüss type. By fixing the values of functions, specific situations derived from previously established findings are shown. The ultimate purpose of this work is to investigate the Grüss-type integral inequalities with the Saigo k-integral operator, a more generalized integral operator. We also elaborate on a few more outcomes and specific instances of the primary findings.